Effects of a health education intervention on knowledge and attitudes towards chronic non‐communicable diseases among undergraduate students in Jordan - Maysa H. Almomani; Mohammad Rababa; Fatmeh Alzoubi; Karimeh Alnuaimi; Ahlam Alnatour; Reem A Ali (Wiley, 2021)
Abstract Aim To assess the effect of a health promotion course on knowledge and attitudes towards chronic non‐communicable diseases (CNCDs) among undergraduate students in a Jordanian university. Design A one‐group pre‐test-post‐test study design was used. Methods A convenience sample of 178 undergraduate students registered in a 3‐credit health promotion course was enrolled in the study and completed both pre‐ and post‐tests. This course is offered as an elective course for undergraduate students by the Faculty of Nursing at a large public university in Jordan. Twelve, one‐hour interactive sessions regarding CNCDs topics were delivered over 3 weeks as part of the health promotion course. A computer‐based questionnaire was used to evaluate students' knowledge and attitudes towards CNCDs including diabetes, hypertension and cancer, before and after undertaking the course. Results There was a significant improvement in the overall knowledge (Cohen's d effect size (d) = 1.08) and attitudes (d = 0.62) among all the students, regardless of gender. The overall knowledge and attitudes scores were significantly higher among females in the pre‐test, but the differences in their overall scores became insignificant in the post‐test. Education on specific topics was effective in improving university students' knowledge and attitudes about health‐promoting behaviours, thereby preventing CNCDs. It is important to incorporate health promotion education regarding CNCDs into university curricula using innovative approaches to enhance healthy behaviours in young adults.